DYNAMICS OF CONFLICT AND EMOTIONAL SUPPORT IN ROMANTIC RELATIONSHIPS: IMPLICATIONS FOR DEPRESSION - Irene, Maria Gabriella; Hindradjat, Juliana (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study investigates the impact of conflict dynamics and emotional support in dating relationships on depression levels, emphasizing their significance for mental health. Method: A cross-sectional survey was conducted involving individuals aged 18 to 35 years. Data collection focused on measuring conflict frequency, emotional support, and their correlation with depression levels. Results: The analysis revealed that conflict frequency in dating relationships has a positive correlation with depression levels, while emotional support shows a negative correlation. These findings align with the Social Stress and Attachment Theory, which suggests that insecure attachment patterns and poor emotion regulation contribute to increased depression vulnerability. Novelty: This study underscores the importance of targeting communication skills and enhancing emotional support in romantic relationships as potential intervention strategies to reduce depression risk among couples.